APPLICATION OF SPATIAL BASED LEARNING MODEL TO IMPROVE GEOGRAPHIC SKILLS AND DISASTER LITERACY IN HIGH SCHOOL STUDENTS - Ayuningtyas, Annisa Rahmawati; Irawan, Listyo Yudha (Abjadia : International Journal of Education, 2024)
The importance of geography skills and disaster literacy is given to high school students with the application of spatial based learning model in supporting quality learning. This study aims to improve students' geographic skills and disaster literacy through the application of spatial based learning model. This research is a type of class action research with the research subject is class XI IPS 1 consisting of 36 students. Data collection was done by collecting students' pretest-posttest scores. The results of this study showed an increase in the average student score from the pre-cycle score of 62.25 to 68.61 in cycle I and 78.89 in cycle II. The increase was also shown by the number of students who met the KKM score of 78% or more than half of the total students in the class. The research was concluded in the second cycle after the scores were able to achieve the objectives of the research. This model is effective as a learning approach that is more interactive and relevant to the surrounding environment of students, so it can be an alternative learning that can be applied to improve the quality of learning in schools, especially in geography subjects.